The Importance of the Family Environment of Trafficking Victims in Peru, Before and After Exploitation - Querol, Andrea; Lerner, Antonia (Anti-Trafficking Review, 2025)
This article analyses the importance of the family environment of victims of human trafficking in Peru, before and after exploitation. Based on interviews with 30 victims and 10 family members, it demonstrates that families, primarily mothers, can play a powerful role in both preventing victimisation and assisting victims to recover from human trafficking experiences. Family structure and background can increase victims’ vulnerability, yet the families are also the ones that protect and take care of victims. However, government officials often blame parents and family members for victims’ exploitation, leading to revictimisation of both victims and their families. Understanding families’ role in victim reintegration is crucial for improving the quality of social inclusion. Protection and care services workers must involve victims’ families as part of their recovery process and receive further training to safeguard survivors’ physical and mental integrity.